Use of transcranial direct current stimulation in poststroke postural imbalance - Tonomura, Tadayasu (BMJ Case Rep, 2021)
Independent gait following stroke is ultimate goal of rehabilitation. Non-invasive neuromodulation achieving it has never been reported. A 74-year-old woman suffered from subarachnoid haemorrhage, followed by hydrocephalus. Both were treated successfully. Even 1 year after the ictus, ambulation was difficult due to truncal instability with lateropulsion mainly to the left side. Transcranial direct current stimulation (tDCS) was applied to the parietal area (2mA for 20 min/day; anode on left side, cathode on right) for 16 days. The intervention improved her truncal instability and she achieved independent gait. tDCS of the parietal area could be a novel treatment option for gait disturbance due to postural instability following stroke.